Activation of P2Y(1) and P2Y(2) receptors induces chloride secretion via calcium-activated chloride channels in kidney inner medullary collecting duct cells - Rajagopal, Madhumitha (American Physiological Society, 2011)
Dysregulation of urinary sodium chloride (NaCl) excretion can result in extracellular fluid (ECF) volume expansion and hypertension. Recent studies demonstrated that urinary nucleotide excretion increases in mice ingesting a high-salt diet and that these increases in extracellular nucleotides can signal through P2Y(2) receptors in the kidney collecting duct to inhibit epithelial Na(+) channels (ENaC). However, under conditions of ECF volume expansion brought about by high-dietary salt intake, ENaC activity should already be suppressed. We hypothesized that alternative pathways exist by which extracellular nucleotides control renal NaCl excretion. We used an inner medullary collecting duct (mIMCD-K2) cell line in an Ussing chamber system as a model to study additional ion transport pathways that are regulated by extracellular nucleotides. When ENaC was inhibited, the addition of adenosine triphosphate (ATP) to the basal side of cell sheets activated both P2Y(1) and P2Y(2) receptors, inducing a transient increase in short-circuit current (I(sc)); addition of ATP to the apical side activated only P2Y(2) receptors, inducing first a transient and then a sustained increase in I(sc). The ATP-induced increases in I(sc) were blocked by pretreatment with a phospholipase C (PLC) inhibitor, a calcium (Ca(2+)) chelator, or Ca(2+)-activated Cl(−) channel (CACC) inhibitors, suggesting that ATP signals through both PLC and intracellular Ca(2+) to activate CACC. We propose that P2Y(1) and P2Y(2) receptors operate in tandem in IMCD cells to provide an adaptive mechanism for enhancing urinary NaCl excretion in the setting of high-dietary NaCl intake.